Similar dysregulation of lupus-associated miRNAs in peripheral blood mononuclear cells and splenic lymphocytes in MRL/lpr mice - Wang, Zhuang (Lupus Sci Med, 2018)
OBJECTIVE: MicroRNAs (miRNAs) play an important role in the pathogenesis of various autoimmune diseases including systemic lupus erythematosus (SLE; lupus). We have previously reported a common pattern of miRNA dysregulation in splenic lymphocytes from several mouse models of lupus. In this study, we investigated whether there is a similar miRNAs expression dysregulation in peripheral blood mononuclear cells (PBMCs) and splenocytes in a classical murine lupus model, MRL/lpr. METHOD: PBMCs were isolated from blood samples of control MRL and lupus MRL/lpr mice aged 14–15 weeks by gradient centrifugation with Histopaque 1083 density media. miRNA TaqMan assays were performed to analyse the expression of 10 lupus-associated miRNAs including miR-182-96-183 cluster, miR-146a, miR-148a, miR-21, miR-31, miR-127, miR-155, and miR-411 in MRL and MRL/lpr PBMCs. RESULT: In this study, we found that 8 out of 10 examined miRNAs (miR-21, miR-31, miR-127, miR-155, miR-96, miR-182, miR-183 and miR-411) were similarly dysregulated in both PBMCs and splenocytes of MRL/lpr mice when compared with MRL control mice. Only two miRNAs (miR-146a and miR-148a) showed different dysregulation pattern in the PBMCs and splenocytes of MRL/lpr mice. By comparing with the published miRNA data in human lupus, we demonstrated similarity in miRNA dysregulation in murine and human lupus PBMCs. CONCLUSION: The findings in this study suggest that the miRNA changes observed in PBMCs largely reflect the miRNA dysregulation in cells from the lymphoid organ spleen. Analysis of miRNAs in PBMCs has an advantage over the splenocytes since it allows for monitoring the kinetics of lupus-associated miRNAs expression with peripheral blood cell samples during the development of the disease or after instituting treatment. The similar dysregulation of miRNAs in murine and human lupus PBMCs supports the importance and the feasibility of using murine lupus models to study the pathogenic and therapeutic function of miRNAs in human lupus.